Overcharge Self-Regulated Li-ion Battery Based on LiFePO4 via a Solid State Combined Cathode. (24th January 2017) - Gu, Fei; Jung, Kichang; Lim, Taehoon; Martinez-Morales, Alfredo A.
ABSTRACT: Safety is one of the most crucial problems faced by the lithium-ion battery (LIBs) industry. In this work, we propose a strategy to avoid overcharging of a battery via the application of a solid-state combined cathode. The goal of this research is to produce LIBs with overcharge self-regulation capabilities. In order to achieve self-regulation functionality, 1, 4-di-tert-butyl-2, 5-dimethoxybenzene (DBB) is added to as-synthesized LiFePO4, post synthesis. DBB has a trigger voltage of 3.9 V. When this voltage is reached, DBB forms a reduced ion that is released into the electrolyte from the cathode side. The DBB ion transfers to the anode side where it oxidizes and transfers back to the cathode side. This process forms a redox shuttle and consumes the extra charges keeping the voltage at a safe level (i.e. 3.9 V). The DBB redox shuttle protects the LiFePO4 -based LIBs with working voltage between 3.4 and 3.5 V. The cycleability of assembled batteries is tested using an Arbin Tester.